BRING TO LIGHT STUDENTS LISTENING COMPREHENSION DIFFICULTIES AT TERTIARY LEVEL IN EFL CONTEXT - Murwani Ujihanti; Welly Ardiansyah; Nurul Aryanti (Politeknik Negeri Sriwijaya, 2019)
Abstract: Listening Comprehension has been an obstacle for the students to learn English well. They have untold difficulties in understanding listening text. This paper tries to uncover this problem and the step stone to facilitate teachers finding solution to set the students free from their confinement. 56 students were the respondents of the questionnaire concerning about their listening difficulties. Their biggest responses were limited listening time allocation (10%-25% out of teaching time), failure in listening test (41 students), lack of practice listening at home (46 students), using the right learning media (50 students), No meta-cognitive strategy before listening (30 students), listening to word by word technique while listening (35 students), ignoring the difficult words during listening (29 students), speed of speech (38 students), unfamiliar topic (35 students), and long listening text (25). The conclusion is the awareness of listening comprehension difficulties resulted on identifying the problem. As their attitude toward learning was positive, they were able to apply the right strategy to help them reducing their listening problems.